(1S,2R,7R,8S,10R)-9,9-Dibromo-2,6,6,10-tetramethyl-1α,2α-epoxytricyclo[5.5.0.0(8,10)]dodecane - Benharref, Ahmed (International Union of Crystallography, 2013)
The title compound, C(16)H(24)Br(2)O, was synthesized from the reaction of β-himachalene (3,5,5,9-tetramethyl-2,4a,5,6,7,8-hexahydro-1H-benzocycloheptene), which was isolated from Atlas cedar (Cedrus atlantica) essential oil, after reaction with dibromocarbene. The asymmetric unit contains two independent molecules with similar conformations. Each molecule is built up from fused six-and seven-membered rings and two three-membered rings. In both molecules, the six-membered ring has an envelope conformation with the flap provided by the C atom of the epoxy ring, whereas the seven-membered ring displays a chair conformation. The crystal packing is governed only by van der Waals interactions. The absolute configuration was established from anomalous dispersion effects.